ChemInform Abstract: Trimethylaluminium‐Mediated Reaction of Primary Carboxamides with Amines and Indoles: A Convenient Synthesis of Amidines and Indole‐3‐acylimines. Issue 10 (March 2015) - Velavan, A.; Sumathi, S.; Balasubramanian, K. K.
Abstract A general method for the synthesis of amidines is developed using the AlMe3‐promoted direct coupling of carboxylic amides with primary and secondary amines.